Pemanfaatan Media Digital G Suite For Education dalam Pembelajaran BIPA Jarak Jauh di University Of Vienna - Hilda Septriani (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
The Covid-19 pandemic has affected almost all social structures, including education. Learning Indonesian language for Foreign Speakers (BIPA) is one of the teaching fields that are affected. The targets of BIPA learners to be discussed in this study are Austrian citizens who studied Indonesian language at the University of Vienna for winter semester between 2020-2021. The use of various technological media and digitalization strategies carried out during BIPA teaching is a precise effort that is implemented to deal with the effectiveness of distance learning. The research method that will be used by the author is descriptive analysis and literature study to describe digitalization strategies in online BIPA teaching for students in Austria. The purpose of this study is to identify the utilization of digital media G Suite for Education in online BIPA teaching for students at the University of Vienna. However, the ability to access digital media is still considered difficult by some students in the class. These various digitalization and implementation strategies will be described in more detail in the research results as a representation of the effectiveness of using various technology platforms in the teaching of BIPA.